Mobile Banking Adoption and Financial Inclusion: The Mediating Role of Intention to Use (SOMTU Journal of Business and Management Research, 2025)
This study explores the impact of digital payment on financial inclusion (FI) in Kathmandu Valley, focusing on mobile banking adoption. Grounded in the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), the research examines the influence of perceived usefulness (PU) and perceived ease of use (PEU) on the intention to use mobile banking (IMB) and its subsequent role in enhancing financial inclusion. Additionally, the study explores the mediating effect of IMB in the relationship between these factors and FI. A quantitative approach was employed, using a cross-sectional design to analyze data from 316 mobile banking users in Kathmandu Valley, collected through structured questionnaires. The data were analyzed using Structural Equation Modeling (SEM) to determine the direct and indirect impacts on financial inclusion. The findings reveal that both PU and PEU significantly influence the intention to use mobile banking, which in turn has a substantial impact on financial inclusion. Moreover, the intention to use mobile banking partially mediates the relationship between PU, PEU, and FI. The study underscores the importance for financial institutions to develop user-friendly mobile banking platforms to enhance customer experience and foster greater financial inclusion. By blending TAM and TPB frameworks, this research provides a novel empirical perspective on digital payments and financial inclusion in a developing region.